Thermal stresses of a cubic quasicrystal circular disc. (September 2022) - Long, F.; Li, X.-F.
Abstract: This paper presents a thermoelastic solution for a circular disc made of cubic quasicrystal. Using the semi-inversion method, the thermal stresses are presented when the disc is subjected to temperature change of a quadratic function of radius or constant internal heat source. We find that the displacements and strains in the phonon and phason fields are angle-dependent, while the phonon and phason stresses are axisymmetric and do not rely on the angle. Moreover, the thermal stresses exhibit a parabolic axisymmetric distribution, where the strains display an angle-dependent non-axisymmetric behavior. Highlights: Thermoelastic problems of a cubic quasicrystal is studied. The thermal stresses of a circular disc are determined analytically. The thermal stresses are axisymmetric for parabolic temperature change. The thermal strains and displacements are angle-dependent.